2006
DOI: 10.1002/adma.200502194
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Transport and Thermoelectric Properties of Individual Polycrystalline Bismuth Nanowires

Abstract: Nanofabrication methods and a device architecture are combined to allow for four‐point electric, thermoelectric, and electric field‐effect measurements on individual Bi nanowires. The figure shows a false‐color SEM image of a typical device used in this study, with the 11 Bi nanowires shown as a red → white gradient. The temperature dependence of the various transport properties as a function of nanowire width is investigated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
164
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(169 citation statements)
references
References 51 publications
(80 reference statements)
5
164
0
Order By: Relevance
“…Unfortunately, despite much progress in the study of thermoelectric properties of nanomaterials, [7][8][9][15][16][17] there is no experimental work showing that the sharply peaked DOS in 1D or 0D materials can indeed be used to tailor the thermoelectric properties. In carbon nanotubes (CNTs)…”
mentioning
confidence: 99%
“…Unfortunately, despite much progress in the study of thermoelectric properties of nanomaterials, [7][8][9][15][16][17] there is no experimental work showing that the sharply peaked DOS in 1D or 0D materials can indeed be used to tailor the thermoelectric properties. In carbon nanotubes (CNTs)…”
mentioning
confidence: 99%
“…Silicon Germanium (SiGe) has been shown to be reliably manufactured, but at the cost of an inferior performing TEG, albeit experimental and theoretical evidence has shown that SiGe nanowires TEG efficiency can be improved, by changing the doping and nanowire size. This is because manufacturing methods for this technology is far more developed and matured, and so its production is far more reliable [19] This meta-study has also highlighted a need for researchers to include more data in their papers or for data not entirely relevant to the paper be easily accessible for peer review and further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is a result of the increased phonon scattering from the lower CSD of the wire which results in a shorter distance to travel before reflected phonons at the boundary interfere. Reduced electron transport which is the larger component of thermal transport also contributes to the reduction [19].…”
Section: Thermal Conductivity Vs Csdmentioning
confidence: 99%
See 1 more Smart Citation
“…NWs, many published works indicate that the idea of studying pure Bi and Bi based crystals as a material with promising thermoelectric efficiency and high sensitivity to pressure is still attractive [2][3][4][5][6][7]. The prospect of the thermoelectric application of NWs will require the ability to control their parameters.…”
mentioning
confidence: 99%